PENGARUH LAYANAN BIMBINGAN PRIBADI DAN LAYANAN BIMBINGAN KARIR TERHADAP PEMAHAMAN DIRI SISWA - Astuti, Dwi; Mudjijanti, Fransisca (Educatio Vitae, 2015)
Personal counseling services and career guidance services are services provided guidance and counseling counselor to students. One of the purposes of the provision of these services is that students are able to understand him very well so that students succeed in reaching the goal - his. Therefore, understanding themselves into component very important for students. This study aimed to determine the effect of personal guidance and career counseling services to student understanding. The population in this study is a class XII student of SMA Negeri 1 Ponorogo Slahung academic year 2014/2015 amounted to 143 students and is divided into 7 classes. The sample in this study was 80% of the population are five classes (115 students). The sampling technique used is the author of Random Cluster. Data obtained by using questionnaires shaped scale is a scale private tutoring services, career guidance services scale, and the scale of student understanding. In this study, the authors propose three hypotheses, namely: 1) The first minor hypothesis: there is a significant effect of personal counseling services to students' self-understanding. 2) The second minor hypothesis: there is a significant effect of career guidance services to the student's self-understanding. 3) The major hypothesis: there is a significant effect of personal guidance and career counseling services to students' self-understanding. Data were analyzed using multiple linear regression techniques. Model regression equation Y = -8.293 + 0.643 (X1) + 0.533 (X2). Further results of analysis show that: 1) There is a significant effect of private tutoring services to students' self-understanding which proved to t = 6.531 and t table = 1.980. 2) There is a significant influence of career guidance services to the self-understanding of students, who proved t = 7.214 and t table = 1.980. 3) There is a significant effect of personal guidance and career counseling services to students' self-understanding, which proved F count = 56.421 and F table = 3.09. Based on these results can be summarized as follows: 1) for t> t table then the first minor hypothesis is accepted. 2) for t> t table then the second minor hypothesis is accepted. 3) since F count> F table, the major hypothesis is accepted.